The Influence of Transformational Leadership Style and Work Environment on Employee Performance in Retail Companies - Rahman, H Abd; Rahman, A Syafir; Sulfiani, Sulfiani; Kamaruddin, Kamaruddin; Sahabuddin, Sahabuddin (International Journal of Economics (IJEC), 2025)
This study examines the influence of transformational leadership style and work environment on employee performance within retail companies. The research aims to provide comprehensive insights into how leadership behaviors and environmental factors contribute to enhanced employee performance in retail settings. This qualitative research employs a comprehensive analysis utilizing in-depth interviews, focus group discussions, and thematic analysis to explore the relationships between transformational leadership, work environment, and employee performance. The study examines Bass's four dimensions of transformational leadership (idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration) and their interaction with various work environment factors. The analysis reveals that transformational leadership significantly influences employee performance through its four core dimensions. The work environment, encompassing both physical and psychological elements, serves as a crucial moderating factor in this relationship. The study identifies key themes including leadership authenticity, environmental supportiveness, employee empowerment, and performance enhancement mechanisms. The findings provide valuable insights for retail managers and human resource professionals to develop effective leadership strategies and create supportive work environments that optimize employee performance. The research offers practical guidance for implementing transformational leadership practices in retail contexts. This study contributes to the existing literature by providing a comprehensive qualitative analysis of the interaction between transformational leadership and work environment in influencing retail employee performance, offering new perspectives on leadership effectiveness in retail settings.